Lived experiences of religious moderation among multicultural muslim communities - Reizki Maharani; Rizki Ramadhan; Khairul Amri (Asian Journal of Islamic Studies and Society, 2024)
Religious moderation has emerged as a critical framework for sustaining social harmony within Indonesia's increasingly diverse urban communities. This study explores the lived experiences of multicultural Muslim communities in Pekanbaru, Riau, in practicing religious moderation and cultivating social tolerance. Employing a qualitative phenomenological approach, this research engaged 20 key informants selected through purposive sampling from a population of approximately 300 multicultural Muslim residents in Pekanbaru. Informants represented diverse social roles including religious leaders, community figures, Muslim youth, university students, educators, and general public members. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using thematic analysis guided by the Miles and Huberman interactive model. Four major themes emerged from the analysis: (1) Islamic values as the foundation of social harmony, (2) lived experiences of religious moderation in multicultural settings, (3) practices of social tolerance and mutual respect, and (4) community resilience through collective moderation. Triangulation through source, method, and member checking confirmed the trustworthiness of findings. The study reveals that religious moderation in Pekanbaru is not merely a theological concept but a lived social practice rooted in Islamic teachings of brotherhood, compassion, and balanced conduct. These findings contribute to the theoretical understanding of how Islamic moderation operates at the grassroots level and offer practical implications for community development, Islamic education, and multicultural policy in Indonesian urban contexts.